Greenhouse gas emissions and mitigation options for German wine production. (1st March 2019) - Ponstein, Helena J.; Meyer-Aurich, Andreas; Prochnow, Annette
Abstract: In the light of a dire need to reduce greenhouse gas emissions (GHG) from food value chains, this paper analyses GHG emissions from wine production based on primary data from 5 wineries, one wine cellar and 9 grape producers in Germany and explores main emission sources based on their contributions to variance. Considering system boundaries from cradle to gate we found a 90% confidence interval for results between 0.753 and 1.069 kg CO2 e per bottle of wine. Main contributors to variance were bottle weight (31%), electricity usage (18%), heat (11%), yield (−9%), and diesel use in vineyards (9%). Looking at production process phases, 19% of emissions resulted from the production of wine grapes, while 81% were attributable to the winery phase, mainly to the packaging materials (57%). Exploring the mitigation potential of a reduction in bottle weight, reuse of glass bottles, increase in packaging volume and renewable energies, we found that the reuse of glass bottles deserves close attention from wine producers, consumers, and policy makers who strive for an effective decarbonization of the wine value chain. The mitigation potential of the reuse of an average bottle exceeds the mitigation potential from a reduction in bottle weight by more than threefold. A combination of the replacement of grid electricity by renewable energies, bottle weight reduction and reuse can curb GHG emissions per bottle of wine by 47%. Highlights: 90% confidence interval for results between 0.753 and 1.069 kg CO2 e per 0.75 L wine. Most influential emission sources: bottles, electricity, heat, fuel use. Besides reduction in weight the reuse of glass bottles is a key mitigation option. GHG reductions of 45% possible with reuse of the glass bottle and renewable energy. Findings are transferable to beverages other than wine in glass packaging.